KAJIAN SIFAT FISIK TANAH DAN BERBAGAI PENGGUNAAN LAHAN DALAM HUBUNGANNYA DENGAN PENDUGAAN EROSI TANAH - Arifin, Moch. (MAPETA, 2010)
Physical of soil is one of the factors that affect the value of land erosion besides management of vegetation, organic materials and slope. Transformation of land use arrangement is very affecting at degradation of land and the height of erosion. This study aims to examine whether there are changes in the soil physical of the land in relation to the value of erodibility and against land erosion value. This research was conducted in Kabupaten Kediri many kind of land use, forests, alley cropping and monoculture. Erosion value is calculated according to USLE (Universal Soil Loss Equation) methode. The results of the research obtained that forest have a erosion 12.1 tons / ha / that can be criteria on medium danger erosion, while the monoculture and alley cropping have a height erosion level with a value erosion 17.6 tons / ha / year and 51.45 tons / ha / year.Key words : Soil physical, land use, erosion value